Effect of Particles Content and Size on Density, Void and Tensile Properties of Sokka-Clay/Phenolic Composite - Diharjo, Kuncoro; C. N. Nyoto Saputro, Yudit; ., Triyono (International Journal of Engineering and Technology, 2018)
Sokka clay particles, whose stability in mass and good inhibitor in flame, is capable to be used as filler in polymer composite. The investigation on tensile properties of Sokka-clay/phenolic composite at different particles content (0-50 vol%) and size (less than 74 Âµm up to 177 Âµm) has been performed. The analysis of chemical compound, voids fraction, density and fracture surface was conducted to complete the discussion. The Sokka-clay/phenolic composites have an increase in density along with an increase of particle content and a decrease of particle size. Voids also rise proportionally with an increases of particles content and size. The particles addition of 10 vol% on phenolic decreases its strength gradually. However, further addition of particles enhances its strength and modulus, and that is also similar with smaller particle addition. Otherwise, its addition causes a decrease of composite strain due to the lower strain of particles. The increase of strength is influenced by many factors, such as the amount of particle, particle size, movement of particle to fill empty space, effective contact of particle surface, and particle aggregation. The modified Sokka-clay particle has good potential to improve composite properties, and many explorations of its properties needed to fulfill the application requirements.Â